Competition between Ambrosia artemisiifolia and Ambrosia trifida: Is there a threat of a stronger competitor?. (17th May 2021) - Savić, Aleksandra; Oveisi, Mostafa; Božić, Dragana; Pavlović, Danijela; Saulić, Markola; Schärer, Heinz Müller; Vrbničanin, Sava
Abstract: Recent reports of the presence of Ambrosia trifida (AT) in areas infested by A. artemisiifolia (AA) in Serbia warn of the impending establishment of a more damaging crop weed. Here, we test the potential competitive effects of these two weed species. We conducted a field competition study in 2016 and 2017 as a replacement series experiment arranged in a split plot, with main plots (20.5 m × 2 m) at total plant densities of 10 and 100 plants/m 2, and sub‐plots (3 m × 2 m) at the proportion of AT to AA of 100:0, 80:20, 60:40, 40:60, 20:80 and 0:100. Individual plant biomass (IPB) for AT was lowest when grown in monoculture, while AA reached its highest IPB in its monoculture. With AT  < 40%, the AT IPB was larger than (2017) or the same as AA (2016). With AT  > 40%, its IPB decreased due to increased intraspecific competition. We obtained the lowest sub‐plot biomass (SPB) of AT + AA in mixtures with 40:60 and 60:40 ratios, and also the highest SPB of other weed species. We show that despite a larger leaf area, AT may not fully replace AA and thus not become a new threat to crops, as it not only suffers from intraspecific competition at high densities, but also from interspecific competition with AA . Therefore, crops may benefit from a stable coexistence of both species as compared to highly dominant AT or AA . Further studies in the presence of crops are needed to confirm this hypothesis.